Right of Foreigners to Acquire Property on Agricultural Land in Serbia after Law on Agricultural Land Amendments from 2017 - Baturan, Luka O (Zbornik radova Pravnog fakulteta u Novom Sadu, 2018)
This paper presents a multidisciplinary analysis, which tries in the most general way to find an answer to the question of how to regulate the right of foreigners to acquire property on agricultural land in Serbia using economic, law and political methodology. A special accent was put on the new legal norms of the Law on Agricultural Land from 2017. The aim of the paper is to determine the allocative effects and effects on the welfare that generate different legal norms, then to examine whether new legal norms are adequately integrated into the Serbian legal system, and to determine the political factors which led to the introduction of these legal norms. It was concluded that the new legal solution would decrease the efficiency of the allocation of resources, and accordingly, the welfare of economic entities will not be sufficiently increased. Also, legal analysis has shown that legal novelties are in collision with the international law, European Union acquis communautaire, but also the Constitution of the Republic of Serbia. Finally, a general conclusion was reached that the best solution from the political, economic and legal point of view would be the elimination of all ownership transfer restrictions of agricultural land to EU citizens (and probably towards other foreigners). This would allow a more efficient allocation of resources and an increase in the welfare of both domestic and foreign citizens, and elimination of redistribution which had been established in the particular interest of lobby groups too.